Medication Adherence Improvement of Patients with Type 2 Diabetes Mellitus - Amila Amila; Evarina Sembiring (Alta Dharma Publisher, 2021)
Type 2 Diabetes Mellitus (DM) is a degenerative disease with long-term medication which needs home care service to enhance patients' obedience to medication compliance. The study aimed to investigate the effect of home care counseling on patients' medication adherence in prescribed medicine use. Methods: The research design was quasi-experimental using pre-test post-test without control group approach. A total of 43 patients with type 2 DM at the outpatient unit of Sari Mutiara General Hospital were selected through consecutive sampling techniques. The patients were given counseling in medicine using home care visits over 24 times in July 2017 and September 2017. Results: Patient adherence evaluation on disease medication was carried out through questionnaire administration before the patient received counseling (pre-test) and received counseling (post-test). Data from the Questionnaire were analyzed using the Wilcoxon test with a confidence level was 95%. Before counseling, the average score of patients was 3.26. However, after counseling was carried out to the patients, the average score was 0.72. In conclusion, there was an increase in patient adherence, i.e., 2.54. It was also obtained that there was a significant difference in patients' adherence to medication use before and after receiving counseling in-home care, with a significance value of 0.000 (p<0.05). It indicated that home care counseling was effective in enhancing their medication adherence. It is suggested that healthcare practitioners carry out monitoring, particularly during therapy, to prevent diabetic complications